Acceptance and commitment therapy for adults with advanced cancer (CanACT): A feasibility randomised controlled trial. Issue 3 (21st December 2018) - Serfaty, Marc; Armstrong, Megan; Vickerstaff, Victoria; Davis, Sarah; Gola, Anna; McNamee, Philip; Omar, Rumana Z.; King, Michael; Tookman, Adrian; Jones, Louise; Low, Joseph T.S.
Abstract: Objective: To understand the feasibility of recruiting people with advanced cancer into a randomised controlled trial of acceptance and commitment therapy (ACT) vs a standardised talking control (TC) and delivering ACT to this population; to explore the acceptability of outcome measures and generate normative data. Methods: This was a feasibility two‐arm randomised controlled trial. Participants were attendees with advanced cancer at one of three hospice‐based day‐therapy units in London, United Kingdom, who demonstrated low scores on the Functional Assessment of Cancer Therapies—General (FACT‐G). The primary end point was 3 months. Results: The recruitment target was 54 participants; 42 people were recruited and randomised to up to eight individual sessions of ACT (n = 20) or TC (n = 22). Eighteen out of 42 (43%) of participants completed the primary outcome at 3 months, and at least one follow‐up was available in 30/42 (71%) participants. An exploratory analysis revealed a non‐significant adjusted mean difference after 3 months in the main outcome FACT‐G of −3.41 (CI = −18.61‐11.79) with TC having better functioning. Over 6 months, the adjusted mean difference between trial arms was 2.25 (CI = −6.03‐10.52) in favour of ACT. Conclusions: It is feasible to recruit people with advanced cancer in a trial of ACT versus TC. Future research should test the effectiveness of ACT in a fully powered trial.